(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
In the Brazilian Amazon is significant diversity of fruit species, the agronomic characteristics of which are still little studied. The objective of this study was to evaluate the influence of tegument coloration on germination and vigor of camu-camu seeds. The seeds were obtained from ripe and healthy fruits coming from population of the Urubu River in Roraima and were classified visually according to the tegument coloration of green, red and brown color. 200 seeds for each class of colors were utilized, evaluating the following biometric characters: length, breadth, thickness and individual mass, obtained with the aid of a digital caliper and precision balance. The experimental design utilized was the completely randomized with three treatments and 10 replications of 20 seeds. The highest means of mass and volume were obtained from brown and red seeds. The brown seeds produce higher content of root dry mass than both the green and red seeds. The physiological quality of camu-camu seeds of the Urubu River is associated with tegument coloration. Seeds with brown tegument have better development, greater growth of seedlings with greater accumulation of dry matter both in the roots and shoots.